Short-Term Metformin Protects Against Glucocorticoid-Induced Toxicity in Healthy Subjects: A Randomized, Double-Blind, Placebo-Controlled Trial - Thierry, Susanne; Peterson, Caspar Joyce; Pfammatter, Stéphanie; Tardio, Patricia Arroyo; Meier, Christian; Delko, Tarik; Iten, Vasco; Zuern, Christine S; Kühne, Michael; Epstein, Michael; Othman, Alaa; Zamboni, Nicola; et al. (Diabetes care, 2025)
Glucocorticoids (GCs) are potent anti-inflammatory drugs, but strategies to prevent side effects are lacking. We investigated whether metformin could prevent GC-related toxicity and explored the underlying mechanisms.OBJECTIVEGlucocorticoids (GCs) are potent anti-inflammatory drugs, but strategies to prevent side effects are lacking. We investigated whether metformin could prevent GC-related toxicity and explored the underlying mechanisms.This single-center, randomized, placebo-controlled, double-blind, crossover trial compared metformin with placebo during high-dose GC treatment in 18 lean, healthy, male study participants. The trial was conducted at the University Hospital Basel, Switzerland. Participants received prednisone 30 mg/d in combination with metformin or placebo for two 7-day periods (1:1 randomization). The primary outcome, change in insulin sensitivity, was assessed using a two-sided paired t test. Before and after each study period, we conducted a mixed-meal tolerance test, blood metabolomics, and RNA sequencing of subcutaneous adipose tissue biopsy specimens.RESEARCH DESIGN AND METHODSThis single-center, randomized, placebo-controlled, double-blind, crossover trial compared metformin with placebo during high-dose GC treatment in 18 lean, healthy, male study participants. The trial was conducted at the University Hospital Basel, Switzerland. Participants received prednisone 30 mg/d in combination with metformin or placebo for two 7-day periods (1:1 randomization). The primary outcome, change in insulin sensitivity, was assessed using a two-sided paired t test. Before and after each study period, we conducted a mixed-meal tolerance test, blood metabolomics, and RNA sequencing of subcutaneous adipose tissue biopsy specimens.Metformin improved insulin sensitivity as assessed by the Matsuda index (n = 17; mean change: -2.73 ± 3.55 SD for placebo, 2.21 ± 3.95 for metformin; mean difference of change -4.94 [95% CI, -7.24, -2.65)]; P < 0.001). Metabolomic and transcriptomic analyses revealed that metformin altered fatty acid flux in the blood and downregulated genes involved in fatty acid synthesis in adipose tissue. Metformin reduced markers of protein breakdown and bone resorption. Furthermore, metformin downregulated genes responsible for AMPK inhibition and affected GLP1 and bile acid metabolism.RESULTSMetformin improved insulin sensitivity as assessed by the Matsuda index (n = 17; mean change: -2.73 ± 3.55 SD for placebo, 2.21 ± 3.95 for metformin; mean difference of change -4.94 [95% CI, -7.24, -2.65)]; P < 0.001). Metabolomic and transcriptomic analyses revealed that metformin altered fatty acid flux in the blood and downregulated genes involved in fatty acid synthesis in adipose tissue. Metformin reduced markers of protein breakdown and bone resorption. Furthermore, metformin downregulated genes responsible for AMPK inhibition and affected GLP1 and bile acid metabolism.Metformin prevents GC-induced insulin resistance and reduces markers of dyslipidemia, myopathy, and, possibly, bone resorption through AMPK-dependent and -independent pathways.CONCLUSIONSMetformin prevents GC-induced insulin resistance and reduces markers of dyslipidemia, myopathy, and, possibly, bone resorption through AMPK-dependent and -independent pathways.